1999
DOI: 10.7567/jjaps.38s1.360
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Charge and Orbital Ordering by Resonant X-ray Scattering

Abstract: Charge and orbital ordering states of manganites have been observed directly by using synchrotron x-ray diffraction techniques. The alternating pattern of Mn3+ and Mn4+ in charge ordering state was elucidated by the anomalous dispersion method. The orbital ordering at Mn3+ sites is presented based on resonant x-ray scattering near Mn K-absorption edge. The scattering mechanism has been developed by considering the splitting of the Mn 4p levels due to the orbital ordering. The coupling among the charge, spin an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
31
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(35 citation statements)
references
References 0 publications
4
31
0
Order By: Relevance
“…LaMnO 3 the magnetic properties can be understood taking only the predominant JT distortion of the MnO 6 octahedra into account. The double degeneracy of the e g orbitals is lifted by a long-range cooperative Jahn-Teller distortion resulting in an ordering of the d 3r 2 −z 2 orbitals, as argued by Goodenough [48] and Solovyev et al [49] on the basis of theoretical considerations and recently confirmed experimentally by Murakami et al [50]. As a consequence of this JTdriven orbital ordering, the A-type AFM state is established below T N .…”
Section: Phase Diagrammentioning
confidence: 70%
“…LaMnO 3 the magnetic properties can be understood taking only the predominant JT distortion of the MnO 6 octahedra into account. The double degeneracy of the e g orbitals is lifted by a long-range cooperative Jahn-Teller distortion resulting in an ordering of the d 3r 2 −z 2 orbitals, as argued by Goodenough [48] and Solovyev et al [49] on the basis of theoretical considerations and recently confirmed experimentally by Murakami et al [50]. As a consequence of this JTdriven orbital ordering, the A-type AFM state is established below T N .…”
Section: Phase Diagrammentioning
confidence: 70%
“…[25,36] There are many theoretical and experimental studies on the parent compounds, LaCrO 3 , LaMnO 3 , LaFeO 3 , LaCoO 3 , and LaNiO 3 and a range of interfacial and co-doping studies that provide insights into expected spin, charge, and oxygen-mediated coupling types between different 3d transition metal cations across a range of structural distortions and dimensionalities. [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61] These studies provide a starting point to understand nearest neighbor interactions and point to there being a wide range of different spin and exchange interactions coexisting in the high entropy systems; however these previous works provide no direct insights into how magnetism might evolve when combined in a randomly populated system where next nearest neighbors can vary widely.…”
Section: Resultsmentioning
confidence: 99%
“…The crystal structure data thus provide an indirect signature of orbital ordering consistent with the A-type spin ordering. It should be noted that recently developed resonant X-ray scattering tools 66 have identified that the x 2 -y 2 orbital-ordered state is stable in the perovskite Nd 0.45 Sr 0.55 MnO 3 , a material that adopts the A-type magnetic structure. 67 Finally, since we know that for 0.8 < x e 1.0 anisotropic 3y 2r 2 orbitals are occupied, it is important to identify and to explore how the system crosses over to occupation of x 2 -y 2 orbitals, perhaps using probes of local structure (e.g., neutron pair distribution function analysis 30,68-70 ) or the above-mentioned resonant X-ray scattering probes.…”
Section: Evolution Of Structure With Dopingmentioning
confidence: 99%